On the use of event studies to evaluate economic policy decisions: A note of caution - Maryam Haji Ali Beigi; Oliver Budzinski (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2012)
Event studies represent an increasingly popular method to evaluate (future) welfare effects of economic policy decisions. The basic idea is to hire the stock market as a referee, i.e. that stock market reactions to the announcement of policy decision are interpreted to contain superior information about the (future) welfare effects of these decisions. This paper investigates the degree of reliability of event studies as a policy programs evaluation method by critically reflecting upon two underlying assumptions. Since both the information superiority and efficiency of financial markets and, in particular, the conclusion from abnormal returns to (future) economic welfare effects consist of considerable interpretation problems, we issue a note of caution: scientists and policymakers should be very reluctant to rely on stock market reactions as a referee on economic policy decisions. Event studies cannot replace thorough theory-driven economic analysis.
Keywords: G14; D81; H00; L40; L50; 330; event studies; abnormal returns; economic policy evaluation; regional free trade agreements; merger control decisions; IMF supported programs